Identification of Ergonomic Hazards in Motorcycle Workers in Maricaya Selatan Village - Asril, Asril; Harun, Nurul Ilmi; Kurniawan, Rama Nur; Aswadi, Aswadi (Universitas Islam Negeri Alauddin Makassar, 2026)
Ergonomics is an important aspect in creating a safe, comfortable, and productive work environment, but is often overlooked in the informal sector, such as motorcycle repair shops. BPJS Employment data shows a significant increase in work accident cases in Indonesia, reaching 370,747 cases in 2023. One of the biggest contributors is work-related muscle and skeletal disorders (Musculoskeletal Disorders/MSDs), which are often found in jobs with non-ergonomic postures. Research Objective: To identify ergonomic hazards faced by motorcycle repair shop workers in Maricaya Selatan Village. Research Method: The research method employed in this study is a descriptive quantitative approach with an observational research design to identify ergonomic hazards among motorcycle repair shop workers in Maricaya Selatan Village. Research Results: Shows that the informal sector such as motorcycle repair shops face significant ergonomic hazards, but are often not handled systematically due to limited facilities and low worker awareness of the importance of ergonomics, the results of the REBA assessment show high (48.6%) and very high (45.7%) occupational hazards, 48.6% of respondents are in the category